Consequences of the Climate Change in Iraq (Global Journal of Human-Social Science, 2022)
The Climate change is a global issue affecting different parts of our planet where we are living However the reasons of climate change and consequences differ at different parts too In Iraq including the Kurdistan Region the reasons for the climate change are due to man-made and natural effects where the rates of CO 2 emission and those of other greenhouse gasses are increasing drastically besides the global warming decrease in the amount of water income in rivers and streams from Turkey and Iran decrease of rain and snow fall increase of population All these have direct impact on the climate and accordingly the consequences are coming harsher and seriously effective on the daily life of the people In this research different man-made and natural effects which directly affect the climate change are presented and described Moreover predictions and recommendations are given to decrease the consequences of the climate change in Iraq among them the status of awareness is one of the main reasons to climate change besides the global warming
Keywords: climate change; annual rainfall; man-made effects; awareness